SPE Eastern Regional Meeting 2014
DOI: 10.2118/171029-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Filtration Properties in Surfactant-Based and Polymeric Fluids by Nanoparticles

Abstract: Currently, there are few available publications regarding the application of nanotechnology in fluid loss control; hence, this technology needs more exploration. During hydraulic fracturing, fracture conductivity damage and other problems associated with excessive leak-off rate can be significantly curtailed by utilizing nano-fluid systems that evolve from further research studies.An experimental study is presented on the application of nanotechnology on filtration properties of surfactant-based fluids (SBF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The trend of both API and HPHT filtration showed the same decreasing trend with the addition of GNP to the base mud. Similar trends have been found by other researchers [ 40 , 41 , 42 ]. These findings demonstrate that GNP might preserve polymer characteristics in order to limit filtrate loss and, as a consequence, enhance drilling mud efficiency after the hot roll process.…”
Section: Resultssupporting
confidence: 92%
“…The trend of both API and HPHT filtration showed the same decreasing trend with the addition of GNP to the base mud. Similar trends have been found by other researchers [ 40 , 41 , 42 ]. These findings demonstrate that GNP might preserve polymer characteristics in order to limit filtrate loss and, as a consequence, enhance drilling mud efficiency after the hot roll process.…”
Section: Resultssupporting
confidence: 92%
“…Meanwhile, Huang et al 17 have also added 35 nm ZnO nanoparticles to VES and found that the nanoparticles and VES micelles form a quasi-cross-linked structure through van der Waals and electrostatic forces, which can improve the viscosity of the VES and reduce filtration. Fakoya et al 18 have added different proportions of SiO 2 particles with particle size of 20 nm to a surfactant system, polymer system, and polymer–surfactant mixed system, studied the effect of adding nanoparticles on the rheology of different systems, and found that the surfactant base liquid with added nanoparticles is more suitable for the exploitation of unconventional oil and gas, effectively reducing the economic cost and reducing damage to the reservoir. Gurluk et al 19 considered the problem that the surfactant base solution cannot be applied when the temperature is above 200 °F.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the size of nanoparticles, the study of their type, stability, and concentration is also critical. These materials are susceptible to any pH, temperature, and ionic strength. , Individual nanoparticles will attract each other, generating aggregates that might significantly impair the drilling fluid’s rheological and filtration characteristics due to poor colloidal stability or an excessive concentration. , Nanoparticles have been used in drilling fluids for various purposes, including viscosity stabilization, wellbore strengthening in shale, reducing water invasion into a borehole, loss circulation prevention, minimizing clay swelling, and preventing the pipe from being stuck. − To achieve these purposes, many additives are utilized, such as carbon nanotubes, GO, zinc oxide, nanosilica, − and CMC nanoparticles. , One of the widely explored nanoadditives that have a crucial impact on the performance of drilling fluids is graphene and its derivatives. Graphene is an atom-thick, 2D-conjugated structure with high conductivity and a huge surface area.…”
Section: Introductionmentioning
confidence: 99%